GEOLOGY OF THE LAKE PETERS AREA NORTHEASTERN BROOKS RANGE, ALASKA. - Reed,Bruce L. (1968)
The Lake Peters area lies in a remote, topographically rugged part of the Franklin Mountains in the northeastern Brooks Range, Alaska. The area is at approximately lat 69 degrees N and long 145 degrees W; Mount Chamberlin is in the southern part. Rocks exposed in the map area include seven formations ranging in age from Devonian or older to Jurassaic. Quarternary surficial deposits overlie Jurassic rocks and six glacial advances are recognized. (Author) Pub. in Geological Survey Bulletin 1236. Prepared in cooperation with Geological Survey, Menlo Park, Calif. Alaskan Geology Branch.